IFPRI key facts series: Agricultural cooperatives - Banda, Chimwemwe; Duchoslav, Jan (International Food Policy Research Institute, 2023)
Highlights •There is an operational agricultural cooperative in every tenth community in Malawi, but they are not well utilized to access markets or services. •Almost no farmers (0.6 percent in 2019/20) receive extension advice through cooperatives. •Although an increasing share of farmers engage in input and output markets, few do so through cooperatives. •Few farmers buy inputs on credit in general, and almost none receive credit from cooperatives. •Farmers who buy inputs from cooperatives do not pay less than farmers who buy inputs elsewhere. •Farmers who sell their produce to cooperatives also do not obtain better prices than farmers who sell to other buyers.